Writing in social spaces : a social processes approach to academic writing - Murray, Rowena (London : Routledge, 2015)
'Writing in Social Spaces addresses the problem of making time and space for writing in academic life and work of the professionals and practitioners who do academic writing. Even those who want to write, who know how to write well and who have quality publications, report that they cannot find enough time for writing. Many supervisors are unsure about how to help postgraduates improve their writing for thesis and publication. Whilst the problem does presents through concerns with'time', it is also partly about writing practices, academic identities and lack of motivation. This book provides a research-based, theorised approach to the skill of writing whilst retaining a link to writing practices and giving immediate yet sustainable solutions to the writing problem. It supplies new theory and practice on: socializing writing-in-progress and writing with others exploring the alternation of conscious and unconscious, internal and external processes in academic writing whilst in a social grouping Applying social processes in the writing process Using case studies and vignettes of writing in social spaces to illustrate the theory in practice, This book is a valuable resource for academics, scholars, professionals and practitioners, as well as researchers at all stages of their career, and in all disciplines'--
Includes bibliographical references and index.
Keywords: Academic writing -- Social aspects